2012
DOI: 10.1246/bcsj.20120028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Understanding of the Adhesive Force between a Metal Oxide Surface and an Epoxy Resin: Effects of Surface Water

Abstract: A mechanism of the adhesion interaction between an aluminum oxide surface and an epoxy resin is investigated by using density-functional-theory (DFT) calculations. To understand effects of adsorbed water molecules on the adhesion interaction, hydroxylated aluminum oxide surfaces with adsorbed water molecules are prepared. Geometry optimization is performed for a model of adhesiveadherend complex, which is comprised of a fragment of epoxy resin and a wateradsorbed aluminum oxide surface. DFT calculations demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 59 publications
5
74
1
Order By: Relevance
“…The water molecules can act as adhesive agents for connecting Al-O octahedral double-sheet layers of the PB nanoribbon as shown in Fig. 1 B and E. Similar adhesion effects of water molecules between a γ-alumina surface and an epoxy resin were also found (20). The DFT results clearly indicate the influence of intercalated water molecules in enhancing interlayer spacings of PB nanoribbons, which provide a hint to understand the splitting observed in the TEM results.…”
Section: Resultssupporting
confidence: 62%
“…The water molecules can act as adhesive agents for connecting Al-O octahedral double-sheet layers of the PB nanoribbon as shown in Fig. 1 B and E. Similar adhesion effects of water molecules between a γ-alumina surface and an epoxy resin were also found (20). The DFT results clearly indicate the influence of intercalated water molecules in enhancing interlayer spacings of PB nanoribbons, which provide a hint to understand the splitting observed in the TEM results.…”
Section: Resultssupporting
confidence: 62%
“…Computational simulations at the molecular level will provide a better insight into the intermolecular forces acting at the adhesion interface. Recent computational studies have revealed the importance of hydrogen bonding in the adhesion of polymer–metal (metal oxide) interfaces and polymer–graphite interfaces under atmospheric or wet conditions . We have theoretically investigated adhesion interactions in the epoxy resin–aluminum oxide interface and the epoxy resin–graphite interface, [22,23] both of which are important from the viewpoint of industrial applications and surface science .…”
Section: Introductionmentioning
confidence: 99%
“…For a better modeling of the interfacial adhesion between polymer adhesives and hydrophilic adherend surfaces, it is essential to consider water molecules located in the adhesion interface under atmospheric conditions. There are quite limited computational studies that treated the moisture‐induced weakening of adhesion at the molecular level . Ogata and Takahashi have analyzed the moist‐induced reduction of adhesion strength between hydroxylated aluminum oxide surface and polymer of epoxy resin in the presence of interfacial water molecules using the hybrid quantum‐classical method .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generally accepted standpoint is that the oxide on a metal sur face forms chemical or hydrogen bonds with adhesive molecules [1][2][3]. In this case, the thickness of the boundary layer between the adhesive and the oxide should be about 1 nm.…”
Section: Introductionmentioning
confidence: 99%